Mitochondrial DNA Mutations in Grade II and III Glioma Cell Lines Are Associated with Significant Mitochondrial Dysfunction and Higher Oxidative Stress - Soon, Bee Hong; Abdul Murad, Nor Azian; Then, Sue-Mian; Abu Bakar, Azizi; Fadzil, Farizal; Thanabalan, Jegan; Mohd Haspani, Mohd S.; Toh, Charng Jeng; Mohd Tamil, Azmi; Harun, Roslan; Wan Ngah, Wan Z.; Jamal, Rahman (Frontiers in Physiology, 2017)
The role of mitochondria in tumorigenesis has regained much attention as it could dysregulate cellular energetics, oxidative stress and apoptosis. However, the role of mitochondria in different grade gliomasis still unknown. This study aimed to identify mitochondrial DNA (mtDNA) sequence variations that could possibly affect the mitochondrial functions and also the oxidative stress status in different grades of glioma cell lines. Three different grades of human glioma cell lines and a normal human astrocyte cell line were cultured in-vitro and tested for oxidative stress biomarkers. Relative oxidative stress level, mitochondria activity and mitochondrial mass were determined by live cell imaging with confocal laser scanning microscope using CM-H2DCFDA, MitoTracker Green and MitoTracker Orange stains. The entire mitochondrial genome was sequenced using the Affymetrix GeneChip Human Mitochondrial Resequencing Array 2.0. The mitochondrial sequence variations were subjected to phylogenetic haplogroup assessmentand non-synonymous sequence changes were analysed for protein pathogenicity prediction using pMUT and PolyPhen2. The Grade II astrocytoma cells showed increased oxidative stress where a high level of 8-OHdG and oxidative stress indicator were observed using cell imaging. Simultaneously, Grade II and III glioma cells showed relatively poor mitochondria functions and increased number of mutations in the coding region of the mtDNA which could be due to high levels of oxidative stress in these cells. These non-synonymous mtDNA sequence variations were predicted to be pathogenic and could possibly lead to protein dysfunction, leading to OXPHOS impairment, mitochondria dysfunction and could create a vicious cycle of oxidative stress. The Grade IV cells had no missense mutation but preserved intact mitochondria and excellent antioxidant defense mechanisms thus ensuring better survival. In conclusion, Grade II and III glioma cells demonstrated coding region mtDNA mutations, leading to mitochondrial dysfunction and higher oxidative stress.